THE ROLE OF PARENTS IN INSTILLING THE VALUES OF PANCASILA TO YOUNG CHILDREN - Ilfiani Alfanisa; Elan Elan; Budi Rachman (Journal of Early Childhood Education (JECE), 2022)
This article aims to provide information about the critical role of parents in instilling Pancasila values in early childhood. Pancasila is used as a way of life, the philosophy of the state, the foundation of the state, and also the State Ideology, which needs to be implemented and upheld in a planned manner both by the organizers and by the state. The method used in this study uses a literature study. Researchers conduct a literature study by collecting books or magazines related to the problem and research objectives. The type of data used is secondary data and uses a data collection method, namely a literature study. This study's results explain that parents' role in instilling Pancasila values is significant because early age is often referred to as The Golden Age. Cooperation from several parties, both from the role of the teacher, the family environment, and the role of parents, is very effective in educating and instilling Pancasila values in children to form a just and wise generation of nations in the future.